Friday Night Disability: The Portrayal of Parent-Child Interactions on Television’s Friday Night Lights - McGrail, Ewa; McGrail, J. Patrick; Rieger, Alicja; Fraser, Amy (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2018)
Studies of television portrayals of parent/child relationships where the child has a disability are rare. Using the social relational theory perspective, this study examines interactions between parents and a young man with a disability as portrayed in the acclaimed contemporary television series, Friday Night Lights. We found a nuanced relationship between the portrayed teen and his parents and a powerful influence of the community on the parent-child relations and family life.